Educating learners with special educational needs in special schools: an interpretative phenomenological study of teachers' experiences - Matebese, Sibongile (Rhodes University, Faculty of Humanities, Department of Psychology)
In 2001, the Department of Education introduced a policy known as White Paper 6: Special Needs Education: Building an Inclusive Education and Training System. This policy was a response to the worldwide call for inclusive education. It aimed to ensure that all learners with special educational needs (LSEN) and who experience barriers to learning are accommodated and taught in mainstream schooling contexts. Implementation of this policy in South Africa has been a challenge, and special schools continue to exist. While research has explored the experiences of teachers who teach LSEN, such studies have focused on teacher experiences in mainstream schools. A few international and South African studies have explored teacher experiences of teaching LSEN in special schools; however, these explore specific aspects of teacher experiences and are outdated. Based on this premise and drawing on a phenomenological approach, this study sought to explore and understand the experiences of teachers who teach LSEN in special schools. Using the semi-structured interview, eight teachers teaching in special schools in a city in the Eastern Cape were recruited and interviewed. Five superordinate themes emerged from the shared experiences, namely, 'personal commitment and the need for a balance', 'recognising the learner at the centre', 'the importance of a holistic approach', 'the ups and downs of teaching LSEN', and 'support is available but limited'. Within these themes, the teachers experienced teaching LSEN as involving more than teaching, as a role guided by the learner, as collaborative, associated with positive experiences and challenges, including an endeavour that they are adequately supported in but simultaneously require more support for. In reflecting on this analysis, this study argues that special schools are necessary; teaching LSEN in special schools is important to teachers, and they feel a responsibility for it. Recommendations for future research include repeating the present study with a different population and methodology, interviewing parents of LSEN and LSEN themselves to gain further insights into special schooling. The study makes key recommendations for special needs education to help ensure that such an educational system is sustained as inclusion is a long way from being realised.
Keywords: Children with disabilities Education -- South Africa; South Africa. Department of Education; Inclusive education -- South Africa; Special education teachers -- South Africa; Special education teachers -- South Africa Interviews; Phenomenological psychology